The Effect of Noni Leaf Extract on Diabetic Mice Ulcer Length and Blood Glucose Level - Hindrianingtyas, Ranum Mellina; Kuswanti, Nur (LenteraBio : Berkala Ilmiah Biologi, 2023)
Diabetes mellitus is a disease causing hyperglycemia. It can be caused by impaired insulin secretion that lead to diabetic ulcers. This research aimed to identify the effect of ethanolic extract of noni leaves (Morinda citrifolia L) on diabetic ulcer length and blood glucose levels in diabetic mice. This was an experimental study with complete randomized design. There were six treatment groups with four repetitions consisting of Dos 1 (extract 250 mg/kg BW), Dos 2 (extract 500 mg/kg BW), Dos 3 (extract 750 mg/kg BW), GLB (Glibenclamide), KP (Positive Control), KN (Negative Control). Blood glucose levels were measured after alloxan induction (H0), the 7th day (H7) and the 14th day (H14). The result of ulcer measurement were presented from the 1st(H1), 7th (H7), 8th (H8), 9th (H9) and the 10th day (H10). Blood glucose levels data were analyzed using the Anova then Duncan tests. Diabetic ulcer length data were analyzed using Kruskal Wallis followed by Mann Whitney tests. The ethanol extract of noni leaves had an effect on blood glucose levels and diabetic ulcer lengths. Dos 2 was the optimum treatment in decreasing blood glucose levels and diabetic ulcer lenghts.